The legume pod borer, M. testulalis, and its principal host plant, Vigna unguiculata (L.) Walp Use of selective insecticidal sprays as an aid in the identification of useful levels of resistance - Jackai, L.E.N. (Elsevier, 1995)
Cowpea varieties were evaluated for resistance to Maruca testulalis using differential insecticide sprays that provided a range of pest densities and crop damage. The latter was expressed as a pod evaluation index, Ipe, which uses the degree of pod production or pod load (PL) and pod damage (PD). The different spray treatments included a monocrotophos spray which does not control the pod borer, one or two sprays of a protective mixture of cypermethrin and dimethoate at different stages in the crop phenology, and full protection with the same mixture. Unsprayed cowpea produces very few pods so it was not included as a treatment. None of the tested varieties was resistant to flower damage, and apart from TVnu 72, the resistant control, none were highly resistant to the borer. Some varieties e.g. MRx nos. 2-85F, 10-85S, 17-85S, 48-85S, 58-85S, 66-85S, 67-85S and Zonkwa Local had relatively high Ipe values, after receiving only one protective spray, and were considered to be moderately resistant. These varieties can either be grown under minimum insecticide protection (i.e. one insecticide spray) to exploit their potential, in the appropriate cropping or agronomic systems which reduce pest densities, or in locations where borer infestation is low. The Ipe statistic is related to larval counts in flowers (Re = 0.74–0.79), thus if larval counts in flowers were not taken, it would suffice as an indirect estimate of the M. testulalis load. This can be done in conjunction with the rapid visual estimate (RVE) of flower infestation and/or damage which is also more time efficient, even if slightly less accurate than direct larval counts.